Dynamic scores: Extending the parameter space of live performance. Issue 2 (1st July 2013) - Sayer, Tim
This article describes the rationale behind the development of a digital performance system that enables a musical ensemble or solo instrumentalist to interact with a generative and reactive visual score, projected in a cinematic environment. A partial feedback loop is setup between the performer and a projection of visual media, which allow the performer to perceive a response to their playing in certain aspects of the projection. The premise underpinning this piece runs far deeper than merely allowing acoustic instruments to interact with technology; it builds on the pioneering work of Benjamin Libet (1916–2007) and challenges the notion of volition and agency in the way performers react and respond to visual stimulus. The performances enabled by this system will not only provide an audience with a stimulating cinematic event but will also provoke the performers to engage in new and unexpected modes of musical behaviour. A prototype of this system is evaluated as a means of developing psychological and philosophical themes around the notion of freewill in interactive audio-visual performance.